2022
DOI: 10.35335/midwifery.v10i4.729
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stunting in Children Under Five in Rural Areas

Abstract: Stunting is a major nutritional problem that will have an impact on social and economic life in society. Stunting is prone to occur in toddlers. Stunting toddlers tend to find it difficult to achieve optimal growth and development potential, both physically and psychomotor. This study is a systematic review using online databases, namely Sciencedirect, ProQuest, Scopus, and Google Scholar. The keywords used are stunting, toddlers, rural areas and their impact. The purpose of the systematic review is to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Other studies in Indonesia also discovered a higher stunting proportion of children under two years old in the countryside than in the city Laksono et al, 2020). A systematic review and meta-analysis reported that stunting in Indonesian villages is strongly affected by maternal education, family income, maternal nutritional knowledge, exclusive breastfeeding, the age of complementary food, adequate zinc and iron, a record of infection, and genetic factors (Purwita et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies in Indonesia also discovered a higher stunting proportion of children under two years old in the countryside than in the city Laksono et al, 2020). A systematic review and meta-analysis reported that stunting in Indonesian villages is strongly affected by maternal education, family income, maternal nutritional knowledge, exclusive breastfeeding, the age of complementary food, adequate zinc and iron, a record of infection, and genetic factors (Purwita et al, 2022).…”
Section: Discussionmentioning
confidence: 97%